Ayurvedic Treatment Regime of Bilateral Polycystic Ovarian Syndrome (AYUSHDHARA, 2025)
In this present case study, 20 years old woman patient consulted the Ayurvedic OPD of M.M.M. Govt. Ayurveda College & Hospital, Udaipur, with the complaint of irregular menses begin shortly after menarche, extra body hairs, lower abdominal pain and generalized weakness. She was advised for ultrasonography (USG) and the findings suggested both ovaries appear normal in 4 size, and showing multiple small peripherally arranged follicles with echogenic ovarian stroma. She was supposed to be treated with traditional Ayurvedic formulations like; Lata karanja beeja churna, Chandraprabha vati, Stanya shodhan mahakashaya, Erand bhrishta haritki and the case was treated for eight months with the goal of relieving symptoms and dissolving the multiple small follicles in the ovaries. In this case study we use only traditional Ayurvedic medicines for the treatment. Patient’s condition was assessed through USG after eight months of treatment for polycystic ovaries which was completely relieved. Therefore, this study was conducted to evaluate one of the treatment regimens for Polycystic ovaries.